Observing anyonization of bosons in a quantum gas - Sudipta Dhar; Botao Wang; Milena Horvath; Amit Vashisht; Yi Zeng; Mikhail B. Zvonarev; Nathan Goldman; Yanliang Guo; Manuele Landini; Hanns-Christoph Nägerl (Nature, 2025)
Abstract Anyons 1,2 are low-dimensional quasiparticles that obey fractional statistics, hence interpolating between bosons and fermions. In two dimensions, they exist as elementary excitations of fractional quantum Hall states 3–5 and are believed to enable topological quantum computing 6,7 . One-dimensional anyons have been theoretically proposed, but their experimental realization has proven to be difficult. Here we observed emergent anyonic correlations in a one-dimensional strongly interacting quantum gas, resulting from the phenomenon of spin–charge separation 8–10 . A mobile impurity provides the necessary spin degree of freedom to engineer anyonic correlations in the charge sector and simultaneously acts as a probe to reveal these correlations. Starting with bosons, we tune the statistical phase to transmute bosons through anyons to fermions and observe an asymmetric momentum distribution 11–14 , a hallmark of anyonic correlations. Going beyond equilibrium conditions, we observed dynamical fermionization of the anyons 15 . This study opens the door to the exploration of non-equilibrium anyonic phenomena in a highly controllable setting 15–17 .